A Novel Coloration of Polyester Fabric through Green Silver Nanoparticles (G-AgNPs@PET) - Hasan, K. M. Faridul; Pervez, Md. Nahid; Talukder, Md. Eman; Sultana, Mst. Zakia; Mahmud, Sakil; Meraz, Md. Mostakim; Bansal, Vipul; Genyang, Cao (Nanomaterials (Basel, Switzerland), 2019)
This paper reports a novel route for the coloration of polyester fabric with green synthesized silver nanoparticles (G-AgNPs@PET) using chitosan as a natural eco-friendly reductant. The formation of AgNPs was confirmed by UV-visible spectroscopy. The morphologies and average particles size of G-AgNPs was investigated by transmission electron microscope (TEM) analysis. The uniform deposition of G-AgNPs on the PET fabric surface was confirmed with scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy. The thermal properties were investigated using a thermogravimetric analyzer (TGA). The coloration and fastness properties of fabric were found to be significantly improved, a result related to the surface plasmon resonance of G-AgNPs. The antibacterial properties of fabric were also found to be excellent as more than 80% bacterial reduction was noticed even after 10 washing cycles. Overall, the proposed coating process using green nanoparticles can contribute to low-cost production of sustainable textiles.